Peran Produk Inovatif Cibay dalam Peningkatan Daya Saing UMKM Pawon Bu Tina di Kelurahan Kutisari - Wardani, Anisa Setyo; Swasti, Ika Korika (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Improving the competitiveness of SMEs is becoming increasingly important in the era of global competition. One strategy that can be used to improve the competitiveness of SMEs is to develop innovative products. This study aims to determine the role of the innovative cibay product in improving the competitiveness of the Pawon Bu Tina SMEs in the Kutisari Village. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews, observation, and documentation. The results of the study showed that the innovative cibay product has successfully improved the competitiveness of the Pawon Bu Tina SMEs in the Kutisari Village. This is indicated by increased sales, customer satisfaction, and business image. The increase in cibay sales is caused by several factors, namely the better taste, more affordable price, and more attractive packaging design. The increase in customer satisfaction is caused by several factors, namely innovative and attractive products, as well as good service. The increase in business image is caused by several factors, namely recognition from the government and the media, as well as customer trust. Thus, the innovative cibay product is an effective strategy to improve the competitiveness of SMEs.